Pengukuran E-Readiness Menggunakan Framework Stope Pada Penerapan Tilang Elektronik Kota Manado - Oktoverano Lengkong; Kevin Likuayang; Garren Rondonuwu (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2023)
The means of transportation have played an important role in the development of North Sulawesi. With the number of vehicles, the number of traffic accidents increases, which results in an increase in the number of traffic accidents. However, in the current pandemic situation, traffic units are experiencing certain problems. Therefore, to prevent traffic violations, the police have implemented the Electronic Traffic Law Enforcement (ETLE) System. However, this system has the possibility of problems that could interfere with its performance. Therefore, it is necessary to measure the level of readiness for implementing this system. One of the measurements is to use E-Readiness and the STOPE framework as the measurement method. This research was conducted using a qualitative approach with the ATLAS.ti software. The results showed that the overall STOPE grade value was 3.174/4, which means that the E-Readiness level of the application of ETLE at the North Sulawesi Police Ditlantas is at level 3 (Good) based on the five-class scale contained in the STOPE framework.